„Zły” i „dobry” postmodernizm, czyli w jakich czasachżyje współczesny teolog - Kowalczyk, Dariusz (Warszawskie Studia Teologiczne, 2019)
The times we live in are sometimes referred to as postmodern. This is not a precise term. It points more to the negation of what had been than to building a new identity. In any case, a theologian who wants to critically and creatively reflect on the faith of the Church today should take into account the postmodern mentality of modern people. Increasingly, we are dealing in the Church not with the type of pilgrim who is looking for adequate means to reach the goal, i.e. salvation, but with the type of a stroller whose religiosity is spontaneous, fluid, and unordered. Postmodernism is most often seen as negative from the point of view of Catholic faith and morality. It should be noted, however, that in its various currents there are positive elements that a theologian can fruitfully incorporate into his considerations. For example, postmodern criticism does not have to be a relativization of dogmas and commandments, but a concern for freedom and authenticity of the relationship with God. “Good” postmodernism is not about undermining objective truth, but about avoiding encapsulating the truth in totalizing narratives that do not evoke hope and joy. The truths of the Christian faith do not create a system closed once and for all. The mysteries of the Holy Trinity, Incarnation and Grace are an invitation to constantly transcend philosophical and religious discourses. The above considerations become more complicated if we realize that today we are often dealing with postmodern apparent relativism. Relativizing “old” truths is accompanied not by greater “freedom”, but by the creation of new Neo-Marxist systems that strive for a kind of soft totalitarianism.